Eco-cities of tomorrow: how green finance fuels urban energy efficiency—insights from prefecture-level cities in China - Jiaomei Tang; Kuiyou Huang (Energy Informatics)
Abstract Green finance plays a pivotal role in advancing sustainable urban development by enhancing energy efficiency and supporting low-carbon transitions. This study empirically demonstrates that green finance maturity (GFM), which reflects the development and effectiveness of green financial systems, has a significant positive impact on urban energy efficiency (UEE). Using panel data from Chinese prefecture-level cities spanning 2006 to 2021, the analysis shows that a one-unit increase in GFM improves UEE by 0.221 standard deviations. Mechanism analysis reveals that this effect is primarily mediated through technological advancements and improvements in innovation capacity. Further heterogeneity analysis highlights that GFM’s impact is more pronounced in non-resource-based cities and in regions characterized by advanced financial systems, greater global market integration, and higher levels of urbanization. These findings offer valuable, context-specific insights for policymakers seeking to leverage green finance maturity as a tool to promote sustainable urban development across diverse socio-economic and institutional settings.